Salivary calcium level during lactation - Karama MT Al-Nuaimy; Tahani A Al-Sandook (University of Mosul, College of Dentistry, 2006)
Abstract Aims: To determine the salivary calcium during lactation in females and compare with non-lactating females. The saliva nowadays is considered as good source or media for estimation of several ions such as calcium, magnesium, copper, zinc and even abused drug. Materials and Methods: The unstimulated saliva was collected from sixty females, thirty lactating and the other thirty were non- lactating. Results: Salivary calcium ion concentration in non-lactating females was 5.021 + 0.1 compared to 2.46 + 0.21 in lactating mothers that reflect a significant decline in calcium concentration (p < 0.001). Conclusion: This decline in calcium concentration reflected the importance of external calcium supplement during lactation